Evaluation of hearing performance in patients with oral submucous fibrosis in relation to different grades - Rahul Srivastava; Hiroj Bagde; Pallavi A Thomas; Syed B Ahmed; Dhirendra K Singh; Manish K Tiwari (Wolters Kluwer Medknow Publications, 2023)
Background: OSMF is now recognized worldwide as an Indian disease. Blanching and rigidity of the oral mucosa, impaired mobility of the soft palate and tongue, difficulty opening the mouth, burning sensation, lack of gustatory sensation, and mild deafness due to Eustachian tube dysfunction. Soft palatal muscles often affect Eustachian tube function. Materials and Methods: Rama Dental College Hospital and research center Kanpur conducted a cross-sectional study. 60 OSMF patients were randomly selected for this study. Visible light was used for a detailed case history and clinical examination. OSMF was diagnosed by difficulty opening the mouth, blanched oral mucosa, and palpable fibrous bands. Burning, salivation, tongue protrusion, habits, and malignant changes were also diagnostic. ENT specialists used pure tone audiometry to examine the ear (PTA). Results: Out of 60 patients 59 were males and 1 female. The participants who took part in this study ranged in age from 18 to 65. Pure tone audiometry of 120 years, 84 (70%) revealed normal hearing, 10 (8.33%) revealed minimal hearing loss, 14 (11.67%) revealed mild hearing loss and 12 (10%) revealed moderate hearing loss. Conclusion: In order to improve the success rate of treatment, the protocol for managing OSMF patients should therefore include ENT consultation and hearing impairment treatment.